Enhanced production of 2, 3-butanediol by engineered Saccharomyces cerevisiae through fine-tuning of pyruvate decarboxylase and NADH oxidase activities. Issue 1 (December 2016) - Kim, Jin-Woo; Kim, Jungyeon; Seo, Seung-Oh; Kim, Kyoung; Jin, Yong-Su; Seo, Jin-Ho
Abstract Background 2, 3-Butanediol (2, 3-BD) is a promising compound for various applications in chemical, cosmetic, and agricultural industries. Pyruvate decarboxylase (Pdc)-deficientSaccharomyces cerevisiae is an attractive host strain for producing 2, 3-BD because a large amount of pyruvate could be shunted to 2, 3-BD production instead of ethanol synthesis. However, 2, 3-BD yield, productivity, and titer by engineered yeast were inferior to native bacterial producers because of the following metabolic limitations. First, the Pdc-deficient yeast showed growth defect due to a shortage of C2 -compounds. Second, redox imbalance during the 2, 3-BD production led to glycerol formation that lowered the yield. Results To overcome these problems, the expression levels of Pdc from a Crabtree-negative yeast were optimized inS. cerevisiae . Specifically, Candida tropicalis PDC1 (CtPDC1 ) was used to minimize the production of ethanol but maximize cell growth and 2, 3-BD productivity. As a result, productivity of the BD5_G1CtPDC1 strain expressing an optimal level of Pdc was 2.3 folds higher than that of the control strain in flask cultivation. Through a fed-batch fermentation, 121.8 g/L 2, 3-BD was produced in 80 h. NADH oxidase fromLactococcus lactis (noxE ) was additionally expressed in the engineered yeast with an optimal activity of Pdc. The fed-batch fermentation with the optimized 2-stage aeration control led to production of 154.3 g/L 2, 3-BD in 78 h. The overall yield of 2, 3-BD was 0.404 g 2, 3-BD/g glucose which corresponds to 80.7% of theoretical yield. Conclusions A massive metabolic shift in the engineeredS. cerevisiae (BD5_G1CtPDC1_nox) expressing NADH oxidase was observed, suggesting that redox imbalance was a major bottleneck for efficient production of 2, 3-BD by engineered yeast. Maximum 2, 3-BD titer in this study was close to the highest among the reported microbial production studies. The results demonstrate that resolving both C2 -compound limitation and redox imbalance is critical to increase 2, 3-BD production in the Pdc-deficientS. cerevisiae . Our strategy to express fine-tunedPDC andnoxE could be applicable not only to 2, 3-BD production, but also other chemical production systems using Pdc-deficientS. cerevisiae .